Normative self-perceptions of journalists in Nigeria : the case of the Guardian newspaper - Tiri, Judith (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2014)
The study aims at interrogating the self - perceptions of journalists in Nigeria. The study is an attempt to answer some questions as: what contributions have journalists made to the democratization of Nigeria from 1960 to date? What role(s) did the media play during and after the transition to democracy? To what extent have the activities of politicians and the business class affected t he media's social responsibility? What are the self-perceptions of journalists working in Nigeria's The Guardian newspaper? The studies on normative theories of the press, Journalism Culture, and the perceived influences on journalism practice in a democra cy were adapted to answer the afore-listed questions. The works on how elite continuity and transitology models affect the perceptions of journalists in new democracies were also used to answer the questions posed. Since the field of research of the preced ing works is the West, the Nigerian experience points to issues that were not addressed in the prior studies because of the latter's unique socio-political, historical, economic and ethno-religious structures . The data were collected and analyzed according to the QualitaQualitative paradigm, using in-depth semi-structured individual interviews with journalists working at The Guardian newspaper. The findings suggest that the journalists have made positive contributions to Nigeria's democratization. The journalists that support this thesis claim that the self-perceptions of their role have changed from an adversarial position to a democratically-defined social responsibility role. This is because journalists ensure that government policies are implemented and the iss ues that affect the masses are reported. The findings show that in spite of the shift to democratization some challenges have remained, for example the journalists' lives are not safe ; they collect bribes which are popularly called brown envelopes in Nigeria, write biased stories, and hold partisan relationships with the politicians and entrepreneurial elites and so on. The study acknowledges that democratization is in a continuum and that (the stakeholders or) civil society, journalists, the state and the entrepreneurial elites must contribute to deepen Nigeria's democracy. The study suggests a self-perception theory that uses individual structures and institutions of a country to guide the stakeholders to play roles that will deepen democracy.
Keywords: Guardian (Nigeria); Nigeria -- In mass media; Nigeria -- Politics and government -- In mass media; Newspapers -- Nigeria; Journalism -- Political aspects -- Nigeria; Journalists -- Nigeria -- Psychology